THE FALL OF THE MAN IN F. KAFKA’S WORKS - Soghomonyan, Amalya (Armenian Folia Anglistika, 2025)
The early 20th-century literary scene was deeply influenced by Franz Kafka, a writer whose stories explore the intricacies of the human experience, power, and existential anxiety. In modern reality, the problem of man’s fall remains relevant, and Kafka’s artistic experience can help us avoid this ultimate downfall. This article examines the issue of the man’s fall, interpreting sin and its realization as key causes of the hero’s decline. Historical-comparative, psychoanalytical, and philosophical examination methods are applied in the analysis. The article also discusses the Biblical myth, which Kafka sees as the primary cause of humanity’s fall and literary influences that Kafka had. Both Dostoevsky and Nietzsche grappled with the notion of the absurdity of human existence, a theme that Kafka weaves into the very fabric of his narratives. Kafka’s stories, with their surreal settings and illogical events, reflect the absurd and often nightmarish quality of human life that both Dostoevsky and Nietzsche alluded to in their works.